Intense pulsed light for split-second structural development of nanomaterials - Lim, Ho Sun; Kim, Soo Jin; Jang, Ho Won; Lim, Jung Ah (ROYAL SOC CHEMISTRY, 2017)
Recently, intense pulsed light (IPL), also referred to as flash lamp annealing, has gained interest among materials scientists as a highly effective photonic technology for structural reformation and/or chemical modification of various nanomaterials. Split-second exposure of IPL on advanced materials of various compositions, including ceramics, metals, and carbon, and various structures, including nanoparticles, nanowires, and thin films, resulted in dramatic changes in the morphologies and chemical functional groups of the materials. Compared to conventional thermal heating and established photonic technologies such as lasers, IPL technologies have considerable advantages, such as facile equipment set-up, surface-selective treatment, large treatment area, short process times ranging from milliseconds to a few seconds, and roll-to-roll process compatibility. In this review, recent advances in the structural development and/or chemical modifications of various nanomaterials by IPL irradiation will be highlighted.
Keywords: NANOWIRE TRANSPARENT ELECTRODES; SILVER CONDUCTIVE TRACKS; ONE-STEP FABRICATION; COPPER NANOPARTICLES; GRAPHENE OXIDE; DIELS-ALDER; EFFICIENT PRODUCTION; SINTERING TECHNIQUE; HIGH-PERFORMANCE; WHITE-LIGHT